ISSUES FOR FORESTRY RESEARCH NETWORKING IN ASIA - K.G., MacDkicken; Wacharakitti, Sathit (วารสารวนศาสตร์ไทย, 2022)
Deforestation in tropical countries has great impacts to forested area decreasing, species diversities and to national socio-economics. The integrated research networks on multipurposes tree species can foster network research, communication and training for the region. Network development is a time consuming and expensive process, one which demands extensive coordination and communication among interested institutions and individuals. Therefore, integrated research networks on multipurposes tree species supported by the Forestry / Fuelwood Research and Development Project can foster network research, communication and training has been set up to provide a basis and model for expanded collaboration in forestry research in Asia.